Is Telemetry Monitoring Useful in Patients Admitted With Suspected Acute Coronary Syndrome?. (November 2017) - Perkins, Jack; Voore, Naveen K.; Patel, Jaideep; Sanna, Sathish; Mann, Edana; Zakaria, Sammy; Gozu, Aysegul
Patients with a chief complaint of chest pain are frequently monitored by telemetry for evaluation of acute coronary syndrome (ACS). However, there is insufficient evidence to support this practice in younger patients without coronary artery disease (CAD). The objective is to assess outcomes of patients younger than 50 years of age and monitored by telemetry. Consecutive medical records of patients admitted for chest pain between January 1, 2009, and June 30, 2010, were reviewed. Patients were excluded who had a CAD history, an abnormal initial troponin, or an abnormal initial electrocardiogram. The remaining patients' charts were evaluated for adverse events such as death, dysrhythmias, ST-elevation myocardial infarction, or upgrade to a higher level of care. Ultimately, 814 patients were selected for study. No study participants suffered a significant adverse event. When being evaluated for ACS, patients younger than 50 without a history of CAD may not benefit from telemetry monitoring.